Safety efficiency value stream mapping (SEVSM) - A new tool to support the implementation of Lean Safety. Issue 1 (October 2021) - Marques, J P; Sá, J C; Silva, F J G; Pereira, T; Ferreira, L P; Santos, G
Abstract: Occupational health and safety constitutes a topic of great importance in organizations nowadays, given the social and financial implications that arise. In addition to these problems, the manufacturing industry is greatly responsible for the number of accidents at work worldwide. In parallel, organizations focus on improving processes and eradicating waste from production flows. Therefore, there is a need to develop tools which are able to combine these two factors. Metalworking industry suffers of safety problems usually due to the great weight of the parts involved, as well as the processes used. The Safety Efficiency Value Stream Mapping (SEVSM) tool was developed to address these issues with the purpose of facilitating the identification of the risk level at each workstation, which is determined through risk assessment, as well as by verifying the type of risk which causes the security breach, and then indicating the most appropriate Lean tool to be applied for risk resolution. Besides these, it is also possible to obtain a diagnosis of the production flow, enabling an analysis of the most significant production indicators. The results obtained pointed to a 38% reduction in the risk level associated to job preparation activities through the introduction of Total Productive Maintenance, as well as a 31.8% reduction in compressor assembly process time, and 49.3% in the risk level related to the latter through Standard Work.